Can Firm Size as a Moderating Variable Enhance Profitability in Islamic Banks in Indonesia? - Sulistyandari; Kusumah, Alum; Fikri, Khusnul; Bakaruddin (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. This study aims to assess the impact of CAR, NPF, and BOPO variables on the profitability of Islamic commercial banks, considering firm size as a moderating variable. A quantitative methodology is used in this research, where secondary data is collected from the annual financial statements of Islamic commercial banks for the period of 2018 to 2021. The structural equation modelling (SEM) method is used to conduct data analysis. The research findings indicate that CAR has a significant positive effect on profitability, while NPF and BOPO have no significant effect. However, firm size is found to significantly moderate the effects of CAR and BOPO on profitability. The implications of this study highlight the importance of considering firm size in planning the policies and operational strategies of Islamic commercial banks to strengthen the relationship between these factors and the desired level of profitability. This study provides new insights into understanding the factors that influence the profitability of Islamic commercial banks and makes a significant contribution to the literature on Islamic banking.Keywords: Islamic Bank, Profitability, Capital Adequacy Ratio, Non-Performing Financing, Operational Expenses, Operational RevenueAbstrak. Penelitian ini bertujuan untuk mengevaluasi dampak variabel CAR, NPF, dan BOPO terhadap profitabilitas bank umum syariah, dengan mempertimbangkan ukuran perusahaan sebagai variabel moderasi. Penelitian ini menggunakan metodologi kuantitatif dimana data sekunder dikumpulkan dari laporan keuangan tahunan bank umum syariah yang mencakup periode 2018 hingga 2021. Metode Structural Equation Modeling (SEM) digunakan untuk melakukan analisis data. Temuan penelitian menunjukkan bahwa dalam hal profitabilitas, CAR menunjukkan dampak positif yang signifikan, sedangkan NPF dan BOPO tidak menunjukkan pengaruh yang signifikan. Namun, ukuran perusahaan terbukti memoderasi pengaruh CAR dan BOPO terhadap profitabilitas secara signifikan. Implikasi dari penelitian ini menyoroti pentingnya mempertimbangkan ukuran perusahaan dalam perencanaan kebijakan dan strategi operasional bank umum syariah untuk memperkuat hubungan antara faktor-faktor tersebut dan tingkat profitabilitas yang diinginkan. Penelitian ini memberikan wawasan baru dalam memahami faktor-faktor yang mempengaruhi profitabilitas bank umum syariah dan memberikan kontribusi yang signifikan terhadap literatur perbankan syariah.Kata kunci: Bank Syariah, Profitabilitas, Rasio Kecukupan Modal, Pembiayaan Bermasalah, Beban Operasional, Pendapatan Operasional.